The use of psilocybin in the treatment of psychiatric disorders – review - Justyna Woźniak; Rafał Bogacz; Magdalena Gaik; Ewa Uram; Inga Magda; Karol Womperski; Magdalena Osuch (Journal of Education, Health and Sport, 2023)
Introduction: The word “psychedelic” derives from the Greek language and can be loosely translated as “mind manifesting” which is to convey that these substances allow the mind to unleash its hidden potential. Psilocybin is considered to be a “classic psychedelic” and is most commonly found in the form of so-called “magic mushrooms”. Due to its unique properties psilocybin has been used during religious ceremonies and rituals for centuries and more recently also explored in a medical context. Nowadays many studies are being carried out to prove the efficacy of its use in the treatment of various psychiatric disorders.